Making Policy in the Shadow of the Future - Treverton, Gregory F. (RAND Corporation, 2023)
The National Intelligence Council's 2008 report "Global Trends 2025: A Transformed World" projects what the world will look like in 2025 based on recent trends. This paper asks: How should U.S. policy adapt now to account for these trends and the future that will result from them? The author explores such issues as climate change, defense, international relations, and the structure of the federal government.